Case Report: A rare case of intestinal and mucinous-type renal pelvis adenocarcinoma masked by complex renal calculi: a diagnostic dilemma and therapeutic challenge - Xie, Yuning; Sun, Yuchen; Yang, Xianzhen; Che, Xuanyan; Li, Fengyue; Wang, Yifei; Cao, Xiande (Frontiers in Oncology, 2026)
Primary renal pelvis adenocarcinoma (RPA), particularly the mucinous subtype, is an exceedingly rare and aggressive malignancy often associated with chronic inflammation and long-standing calculi, making its diagnosis challenging due to non-specific symptoms mimicking common urological conditions. We present a 79-year-old male patient with a decade-long history of complex nephrolithiasis and recurrent infections, who underwent multiple percutaneous nephrolithotomy (PCNL) procedures. A pivotal diagnostic moment arose during a subsequent PCNL when extensive “purulent moss” was found without significant residual stone fragments, prompting biopsy. Histopathology confirmed high-grade mucinous and intestinal-type adenocarcinoma of the renal pelvis, subsequently managed with laparoscopic radical nephroureterectomy. This case underscores the diagnostic challenge posed by RPA, often masked by chronic calculous disease, emphasizing the critical importance of a high index of suspicion and prompt histopathological evaluation of atypical intraoperative findings (e.g., “purulent moss” instead of expected stone) in patients with complicated urolithiasis, facilitating early diagnosis and improving outcomes.